1993
DOI: 10.1128/iai.61.11.4870-4877.1993
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of corticosteroid-induced suppression of human polymorphonuclear leukocyte-induced damage of Aspergillus fumigatus hyphae by granulocyte colony-stimulating factor and gamma interferon

Abstract: Neutrophils (PMNs) are a critical line of defense against Aspergil1usfinmigatus infection. Increased frequency of invasive aspergillosis has been observed in patients receiving corticosteroids, suggesting a deleterious effect of these compounds on PMN antifungal function. To investigate this hypothesis and to determine the potential preventive utility of granulocyte colony-stimulating factor (G-CSF) and gamma interferon (IFN-y), the effects of hydrocortisone (HCS) and dexamethasone (DXS) on PMN-induced damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…The reason why patients tend to develop IFI following bacteremia is not clear. Known risk factors for IFI, such as prolonged neutropenia, [14][15][16] long-term broad-spectrum antibiotic therapy, 17 the presence of a CVC, 18,19 and the long-term use of corticosteroids 20 were compared between febrile episodes with and without IFI, but no differences were confirmed in this analysis. In this context, bacteremia following febrile episodes during neutropenia appeared to be an independent predictive factor of IFI from those previously identified.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why patients tend to develop IFI following bacteremia is not clear. Known risk factors for IFI, such as prolonged neutropenia, [14][15][16] long-term broad-spectrum antibiotic therapy, 17 the presence of a CVC, 18,19 and the long-term use of corticosteroids 20 were compared between febrile episodes with and without IFI, but no differences were confirmed in this analysis. In this context, bacteremia following febrile episodes during neutropenia appeared to be an independent predictive factor of IFI from those previously identified.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, in vitro studies have demonstrated that G-CSF enhances neutrophil chemotaxis, phagocytosis, and NADPH oxidase activation, 119,120 on the other hand dexamethasone has immunosuppressive effects on the neutrophil function in mice and humans. 121,122 It has been reported that G-CSF/dexamethasone-mobilized neutrophils show a normal ROS production by the NADPH oxidase system and a normal killing of gram-positive and gram-negative bacteria. [123][124][125] Neutrophils from donors that were daily treated with G-CSF injections for 5 days demonstrated reduced chemotaxis in response to serum-treated zymosan, lower levels of lactoferrin, and -at specific effector:target ratios -impaired bacterial killing as compared to neutrophils from matched controls.…”
Section: Granulocytes For Transfusionmentioning
confidence: 99%
“…The latter form is considered to be physiologically active and to have a strong inhibitory effect on the inflammatory process and immune reactions , Johnson et al, 1992, Roth & Kaeberle 1992. Fantuzzi & Ghezzi 1993, Roilides et al, 1993, Salak et al, 1993, Lovallo 1997, Periodontitis is a local inflammatory reaction, often site-specific, in the tooth-supporting tissue leading to a de,struction of the periodontium. An important component of the host response in the pathogenesis of periodontitis is gingival crevicular fluid (GCF).…”
mentioning
confidence: 99%